Phase separation and crystallization in LiNbO3/SiO2 glasses - Prapitpongwanich P. (2014)
Various samples with the compositions (100 - x)LiNbO3·xSiO2 (with x = 10, 20, 25, 30, 35, 40, 50 and 60) were prepared by conventional melting technique. Samples with 20 ≤ x ≤ 35 were transparent, while products with x = 10 or x ≥40 were at least partly opaque under the conditions supplied. TEM-micrographs of replicas gave evidence on phase separation in these glasses. At SiO2-concentrations >30 mol%, the formed structures consist of SiO2-rich droplets in a LiNbO3-rich matrix phase. The size of the structures increases with increasing SiO2-concentration. At an SiO2-concentration of 50 mol%, the droplets are as large as 450 nm. During thermal treatment, the LiNbO3-rich matrix phase crystallizes and forms lithium niobate. © 2008 Elsevier B.V. All rights reserved.